Astronomi dan ibadah - Haron, S.; Abd. Wahab, R.; Zainuddin, M.Z. (2009)
Astronomy closely related to Muslim 's obligation. The knowledge and understanding in astronomy can be applied directly for ibadah purposes. It provides bridge toward determination of p ray er times, hijri calendar for fasting and eid celebration obligation and determination of qiblah direction.